2022
DOI: 10.1111/1759-7714.14417
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment body mass index predicts survival among patients administered nivolumab monotherapy for pretreated non‐small cell lung cancer

Abstract: Background Biomarker assessments for nivolumab monotherapy efficacy in previously treated patients with non‐small cell lung cancer (NSCLC) remain unclear. We evaluated whether body mass index (BMI) and Glasgow prognostic score (GPS) are useful for assessing the efficacy of nivolumab alone as a second‐line treatment in patients with pretreated NSCLC. Methods Data of 99 patients treated with second‐line nivolumab monotherapy for NSCLC between January 2016 and December 2019 were evaluated for prognostic values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“… 117 Furthermore, a study on patients with non-small-cell lung cancer receiving sodium butyrate monotherapy as second-line treatment found that BMI was significantly associated with OS, with higher BMI being associated with longer survival than lower BMI. 118 BMI <18.5 kg/m 2 was independently associated with tolerance to radiotherapy (concurrent chemoradiotherapy; OR 0.36), and intolerance to concurrent chemoradiotherapy was independently associated with poorer survival. 119 However, because smoking is an important risk factor for lung cancer and smokers tend to have a lower BMI, this may confound the association between BMI and cancer survival.…”
Section: Discussionmentioning
confidence: 98%
“… 117 Furthermore, a study on patients with non-small-cell lung cancer receiving sodium butyrate monotherapy as second-line treatment found that BMI was significantly associated with OS, with higher BMI being associated with longer survival than lower BMI. 118 BMI <18.5 kg/m 2 was independently associated with tolerance to radiotherapy (concurrent chemoradiotherapy; OR 0.36), and intolerance to concurrent chemoradiotherapy was independently associated with poorer survival. 119 However, because smoking is an important risk factor for lung cancer and smokers tend to have a lower BMI, this may confound the association between BMI and cancer survival.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies revealed that the BMI was significantly correlated with the OS of patients with NSCLC who were treated with second- or subsequent-line ICIs, as patients with high BMIs experienced more favorable outcomes [ 18 , 31 , 32 ]. While our multivariate analysis revealed that the BMI tended to be associated with OS, the correlation was not significant in our analysis like it was in previous study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies revealed that the BMI was significantly correlated with the OS of patients with NSCLC who were treated with second- or subsequent-line ICIs, as patients with high BMIs experienced more favorable outcomes [ 18 , 31 , 32 ]. While our multivariate analysis revealed that the BMI tended to be associated with OS, the correlation was not significant in our analysis like it was in previous study [ 18 ]. The reason for this inconsistency may be the small number of patients in our study as well as the influence of previous treatments, given that the ICI in our study was administered as a second- or subsequent-line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cancers, like non-small cell lung cancer (NSCLC) and melanoma, have been shown by multiple studies to promote the obesity paradox 16,17,21,82,84,[92][93][94][95] . Other cancers, such as renal cell carcinoma (RCC), have had several studies conducted indicating that obesity is not associated with improved survival, predictive of ICI response, or is even associated with poorer outcome 51,90,91 .…”
Section: The Obesity Paradox and Immune Checkpoint Inhibitors (Ici)mentioning
confidence: 99%